Calculation of proton transfer cross sections in the 14N + 12C reaction at 116 MeV using the DWBA method - Azhibekov, A; Kuterbekov, K. A.; Kabyshev, A. M.; Mukhambetzhan, A. M. (Eurasian Journal of Physics and Functional Materials, 2026)
Calculations of level energies in the shell model of deformed and spherical nuclei are performed for 14N nuclei. The present theoretical analysis of the 12C(14N,13 C)13N reaction at 116 MeV was performed by means of the FRESCO code. Our theoretically calculated di erential cross sections give a fair description of the experimental data for the proton transfer reaction. Based on calculation for 116 MeV predicted calculations for region from Coulomb barrier to a maximum energy available at the DC-60 heavy ion accelerator were made. Recommended Citation Azhibekov, A. K.; Kuterbekov, K. A.; Kabyshev, A. M.; and Mukhambetzhan, A. M. (2020) "Calculation of proton transfer cross sections in the 14N + 12C reaction at 116 MeV using the DWBA method," Eurasian Journal of Physics and Functional Materials: Vol. 4: No. 2, Article 5. DOI: https://doi.org/10.29317/ejpfm.2020040205